A new experimental-numerical approach to estimate peak wind loads on roof-mounted photovoltaic systems by incorporating inflow turbulence and dynamic effects. (1st February 2022) - Estephan, Johnny; Gan Chowdhury, Arindam; Irwin, Peter
Highlights: Rooftop photovoltaic (PV) systems are vulnerable to damage during hurricanes. The effects of low-frequency turbulence are not considered in large-scale testing. Wind-induced dynamic effects are not accounted for in codes and standards. Full- and small-scale wind-tunnel testing was conducted on a rooftop PV panel. Experimental-numerical method is proposed for predicting peak wind loads. Abstract: Building appurtenances, such as rooftop photovoltaic (PV) systems, are vulnerable to damage during extreme wind events. To have more robust designs of PV systems, improved estimation of the peak wind effects is deemed necessary. The overall aim of this research is to develop a method for predicting peak wind loads on PV panels, including dynamic effects. For predicting peak pressures on roofs, the Partial Turbulence Simulation (PTS) method has been previously developed to allow for large-scale model testing by analytically incorporating the effects of the missing low-frequency turbulence based on the quasi-steady aerodynamic theory. The current paper focuses on a new experimental-numerical methodology by advancing the PTS approach to account for the dynamic amplification effects of rooftop PV systems. This is accomplished by mathematically applying a gust transfer function and a mechanical admittance function. The proposed advanced PTS approach is demonstrated using full- and small-scale wind tunnel testing of a PV panel mounted at different locations on the roof of a low-rise building with various tilt angles. The peak net force coefficients obtained from experimental testing of the PV panel were compared with those found in ASCE 7-16. Results showed that the ASCE 7-16 values, which currently do not take into consideration the wind-induced dynamic effects on rooftop PV systems, were significantly lower than the estimated peak force coefficients from the current study. This research describes a methodology for predicting peak wind loads on dynamically sensitive building appurtenances that can be used to inform wind load provisions in standards.